Specific determination of maximal lactate steady state in soccer players - Loures, Joao P. [UNESP]; Chamari, Karim; Ferreira, Eliel C. [UNESP]; Campos, Eduardo Z. [UNESP]; Zagatto, Alessandro M. [UNESP]; Milioni, Fabio [UNESP]; Silva, Adelino S. R. da; Papoti, Marcelo (Lippincott Williams &wilkins, 2015)
The aim of this study was to establish the validity of the anaerobic threshold (AT) determined on the soccer-specific Hoff circuit (AT(Hoff)) to predict the maximal lactate steady-state exercise intensity (MLSSHoff) with the ball. Sixteen soccer players (age: 16.0 +/- 0.5 years; body mass: 63.7 +/- 9.0 kg; and height: 169.4 +/- 5.3 cm) were submitted to 5 progressive efforts (7.0-11.0 km.h(-1)) with ball dribbling. Thereafter, 11 players were submitted to 3 efforts of 30 minutes at 100, 105, and 110% of AT(Hoff). The AT(Hoff) corresponded to the speed relative to 3.5 mmol.L-1 lactate concentration. The speed relative to 4.0 mmol.L-1 was assumed to be AT(Hoff4.0), and the AT(HoffBI) was determined through bisegmented adjustment. For comparisons, Student's t-test, intraclass correlation coefficient (ICC), and Bland and Altman analyses were used. For reproducibility, ICC, typical error, and coefficient of variation were used. No significant difference was found between AT test and retest determined using different methods. A positive correlation was observed between AT(Hoff) and AT(Hoff4.0). The MLSSHoff (10.6 +/- 1.3 km.h(-1)) was significantly different compared with AT(Hoff) (10.2 +/- 1.2 km.h(-1)) and AT(HoffBI) (9.5 +/- 0.4 km.h(-1)) but did not show any difference from LAn(Hoff4.0) (10.7 +/- 1.4 km.h(-1)). The MLSSHoff presented high ICCs with AT(Hoff) and AT(Hoff4.0) (ICC = 0.94; and ICC = 0.89; p <= 0.05, respectively), without significant correlation with AT(HoffBI). The results suggest that AT determined on the Hoff circuit is reproducible and capable of predicting MLSS. The AT(Hoff4.0) was the method that presented a better approximation to MLSS. Therefore, it is possible to assess submaximal physiological variables through a specific circuit performed with the ball in young soccer players.
Keywords: Anaerobic threshold; Blood lactate equilibrium; Specificity; Validation